Investigating the link between temperamental and motor development: a longitudinal study of infants aged 6-42 months - Atsuko Nakagawa; Taishi Miyachi; Makiko Tomida; Taro Matsuki; Satoshi Sumi; Masayuki Imaeda; Akio Nakai; Takeshi Ebara; Michihiro Kamijima (BMC, 2024)
Abstract Background Since the 1920s, motor development has been a strong research theme, focusing on infants' acquisition of motor skills, such as turning over and crawling. In the 1980s, a dynamic systems approach began emphasizing children's own motivation, which helped explain individual differences in the emergence of motor skills. However, few studies have examined factors contributing to individual differences in early motor development. In response, we investigated directional associations between temperament and motor development in children aged 6 months to 3 years. Method The Japan Environment and Children's Study (JECS-A) recruited mothers between January 2011 and March 2014. 2,639 mothers were sent a questionnaire at 6 months, and responses were received from 1,657 of them, with full data for children aged 6 months, 2 years, and 3 years, including from three mothers of twins, were analyzed through structural equation modeling. Question items regarding fine and gross motor activities at each age were selected by pediatric neurologists specializing in developmental disorders. The Japanese version of the Little Developmental Coordination Disorder Questionnaire was administered at 42 months. Temperament was assessed through the parent-reported Behavior Questionnaire (short version) for infants, toddlers, and children. In all three measures, Surgency and Negative Affectivity were extracted, and Effortful Control, a major form of self-regulation, was found from toddlerhood onward, as in previous studies. Results A path diagram reveals that at 6 months, Surgency and Orienting/Regulation interacted positively with the motor function (respectively, r = .57; r = 40, ps < .001). Up to about 3 years, Effortful Control plays a role in facilitating the motor function, resulting in positive effects on Control During Movement (CDM), General Coordination (GC), and Fine Motor Movement (FMM) (β = 14; β = 30; β = 37, ps < .001). Surgency had a positive effect on CDM and GC (β = 18; β = 06, ps < .001), whereas Negative Affect had a negative influence on FMM and GC (β = -.08; β = -.08, ps < .001). Conclusion While Surgency may be a key reactive factor in early motor development, Effortful Control and Movement develop in an interactive manner. Trial registration UMIN000030786. Scientific Title: The Japan Environment and Children's Study. Date of disclosure of the study: 2018/01/15. Only questionnaires were administered in the study.